ANALISIS FRAUD PENTAGON DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Novi Anjar Purwaningtyas; Sri Ayem (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to see the effect of Pentagon fraud on reporting fraudulent financialstatements.The variables of this research are Pentagon Fraud which consists offinancial stability, external pressure, financial targets, nature of the industry,ineffective monitoring, auditor turnover cycle, audit opinion, total accruals, changesin directors, number of CEO photos installed, number of CEO photos installed. ,dualism of positions, good corporate governance and fraudulent financialstatements. The sampling technique was purposive sampling. Secondary datasources. The data collection method uses the documentary method. The analysistechnique used is logistic regression analysis with a significance level of 5%. Theresults showed that financial targets, external certainty, political relations, have apositive and significant effect on fraudulent financial statements. Good CorporateGovernance has a negative and significant effect on fraudulent financial statements.Financial stability, external guarantees, ineffective monitoring, CEO image, dualismof positions, audit opinion have no significant positive effect on fraudulent financialstatements. The nature of the industry, the change of auditors, the change ofdirectors and TATA have a negative and insignificant effect on fraudulent financialreports. Pentagon fraud affected the fraudulent financial statements by 89.4%.10.6% The remaining 10.6% other supporting factors are not included in thisresearch model.